Comparative Analysis of Antimicrobial Efficacy of Sodium Hypochlorite and Chlorhexidine as Irrigants in Root Canal Therapy - Prasad, L Karthik; Markan, Sheenam; Suthar, Mahishi G.; Samal, Sweta; Yaser, Almazyad; Mallikarjun, Elaprolu; Patel, Panthi (Journal of pharmacy & bioallied science, 2025)
ABSTRACT Objective: This research aims to analyze the antimicrobial efficacy of "sodium hypochlorite (NaOCl)" and "chlorhexidine (CHX)" as canal irrigants, evaluating their effects on bacterial load during "Root canal treatment (RCT)". Materials and Methods: In this randomized controlled trial, 80 subjects requiring RCT were included. The participants were randomly allocated into two groups: Group A received 2.5% NaOCl as the irrigant, while Group B received 2% CHX. Microbial samples were gathered from the root canals using sterile paper points both before and after irrigation. The bacterial load was evaluated by counting "colony-forming units (CFUs)" following bacterial culture. Statistical analyzes were conducted using paired t-tests and ANOVA, with a significance level of P < 0.05. Results: Both NaOCl and CHX demonstrated substantial reductions in the bacterial load within the canal system. Group A (NaOCl) achieved a post-irrigation mean CFU count of 1.9 million, reflecting a 96% reduction in bacterial load. Group B (CHX) recorded a mean CFU count of 6.7 million, corresponding to an 86% reduction. The difference in bacterial reduction between the two groups was statistically significant (P < 0.01), indicating that NaOCl was more effective than CHX as an irrigant. Conclusion: Sodium hypochlorite proved to be more efficient than chlorhexidine in reducing microbial counts in root canals. While NaOCl appears to offer superior bacterial reduction, CHX, due to its substantivity and lower cytotoxicity, may still have valuable roles in particular clinical contexts.